ANALISIS FEMINSIME KASUS PERKOSAAN DAN DALIL NEGASI TERHADAP KORBAN SEPERTI TEREFLEKSI DALAM NOVEL THIRTEEN REASONS WHY KARYA JAY ASHER - WONGKAR, GABRIELA MONICA; WANTASEN, ISNAWATY L.; RANUNTU, CHRISTIAN G. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ This research is entitled â€œRape Culture and Victim Blaming as Reflected in the Novel Thirteen Reasons Why by Jay Asherâ€. It is a research that focuses on feminism analysis, particularly about rape culture and victim blaming in the feminism point of view. In this analysis, the writer attempts to analyze the concept of rape culture and victim blaming found in the book Thirteen Reasons Why by looking at the characters, plot, setting but also primarily at the characters: what the person says, what the person doesâ€”including, if possible, what the person thinks, what others (including the narrator of the story) say about the person, what others do (their actions may help indicate what the person could do but does not do), including what they think about others, and what the person looks likeâ€”face, body, clothes. The data were collected from the contemporary best-selling book Thirteen Reasons Why by Asher. In identifying, classifying and analyzing the data, the writer uses the two theories of rape culture and victim blaming of Herman (1984) and Buchwald et. al (2005). The method employed in this research is descriptive method by Verdenbreght (1983). The results of this research shows that rape culture and victim blaming are reflected through the character in the book. Particularly, it is shown through the female characterâ€™s thoughtsâ€”Hannah Baker and her actions also the treatments she had received and had suffered the consequences from the other major and minor characters in the book. Such as treatments from Justin Fooley, Alex Standall, Tyler Down, Courtney Crimsen, Marcus Cooley, and Bryce Walker. The normalization shown in the forms of rape jokes, locker room banter, victim blaming, stalking/ following, non- consensual photos; degradation in the forms of groping and coercion; and assault in the form of the actual rape. Hannah Baker is identified as a victim of rape culture and victim blaming and the other characters are identified as the representation of our society today. A patriarchal society who condones rape culture and victim blaming.Keywords: Keywords: Rape Culture, Victim Blaming, FeminismÂ